The quest for justice in education: capital and funds of knowledge - Gaete, Alfredo; Luna, Laura; Silva-Peña, Ilich; Guerrero, Patricia (Frontiers in Education, 2023)
This paper explores the funds of knowledge approach to pedagogy and educational research from a social justice perspective. In response to the suggestion made by some authors that the approach should be integrated with a capital perspective, we argue that this would work only if the concept of capital is understood in a certain way. Also, and more generally, we try to show that redistribution in education should not be thought of in terms of capital redistribution, but in terms of counteracting structural barriers to participatory parity which result in status differences among citizens. Finally, we suggest three concrete ways this can be achieved through pedagogies based on funds of knowledge.